Supporting and Engaging Families: An Examination of Publicly-Funded Health Promotion Programs in the Intermountain West, USA - Novilla, Lynneth Kirsten; Broadbent, Eliza; Glade, Rozalyn; Crandall, AliceAnn (Frontiers in Public Health, 2020)
Public health programming efforts have traditionally focused on either an individualistic or population approach, neglecting the family as a setting for or partner in health promotion efforts. Due to the multi-faceted influence of families on individual health, family-focused and family-friendly public health interventions are important to making lasting changes for individual and community health. The purpose of this study was to examine the degree to which health promotion programs in a state in the US Intermountain West involve and support families across four family impact principles: family engagement, family stability, family responsibility, and family diversity. A survey was completed by 67 health promotion administrators and practitioners from 12 out of 13 county health departments with additional responses from public health practitioners at the State Health Department. The results of the survey indicated that health promotion efforts were best at supporting family responsibility and a diverse group of families but were weaker in family engagement and family stability. Applying a more family-centered and family-focused approach to health promotion efforts can be achieved by employing interdisciplinary efforts and by taking advantage of tools like the Public Health Family Impact Checklist to intentionally engage and support families in programs and interventions.